2006
DOI: 10.1097/01.lgt.0000192696.93172.ae
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Digitized Cervigrams for Colposcopy Research and Education: Determination of Optimal Resolution and Compression Parameters

Abstract: Our results suggest that 2,000 dpi is the optimal level for digitizing cervigrams, and the optimal compression ratio is 50:1 using a novel wavelet-based technology. At these parameters, pictures have no significant differences with the gold standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…9 Software developed by the National Institutes of Health was used to access and evaluate the images through the Internet. 10 Evaluators were masked to clinical data, because no clinical information was provided.…”
Section: Methodsmentioning
confidence: 99%
“…9 Software developed by the National Institutes of Health was used to access and evaluate the images through the Internet. 10 Evaluators were masked to clinical data, because no clinical information was provided.…”
Section: Methodsmentioning
confidence: 99%
“…After digitization and compression (14), images were evaluated on-line using software developed by the National Institutes of Health (15). The evaluators were 20 colposcopists (12 general gynecologists and 8 gynecologist-oncologists) with at least 10 years of experience in colposcopy and prior research in cervical cancer prevention.…”
Section: Methodsmentioning
confidence: 99%
“…Such a situation was observed in almost half of the patients (46.7%). Comparing these observations to colposcopic pictures of cervical cancer marginal mucosae, the latter was pale rosy to rosy [ 25 ]. Hyperaemia of the underlying tissues and resulting redness of mucosae surrounding cervical tumours was stated in cases of co-existing colpitis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under such circumstances the irregular shapes of cervical mucosal margins and their unclear transition into a colposcopically correct picture of the vaginal portion of uterine cervix become evident [ 22 ]. In extensive exophytic cervical tumours, a colposcopic picture of healthy marginal mucosae may be impossible to obtain [ 22 , 25 ]. Analysis of reports concerning the effectiveness of dermatoscopy in the diagnosis of genital tumours revealed that in cases of invasive vulvar tumours the marginal mucosa contain strongly branched, dilated and elongated pathologic vessels, similar to the margins of invasive OSCC seen with direct oral microscopy and cervical cancers seen in colposcopy.…”
Section: Discussionmentioning
confidence: 99%